2020
DOI: 10.1038/s41598-020-62298-z
|View full text |Cite|
|
Sign up to set email alerts
|

Finding Plastic Patches in Coastal Waters using Optical Satellite Data

Abstract: Satellites collecting optical data offer a unique perspective from which to observe the problem of plastic litter in the marine environment, but few studies have successfully demonstrated their use for this purpose. For the first time, we show that patches of floating macroplastics are detectable in optical data acquired by the European Space Agency (ESA) Sentinel-2 satellites and, furthermore, are distinguishable from naturally occurring materials such as seaweed. We present case studies from four countries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 37 publications
(54 reference statements)
6
211
1
1
Order By: Relevance
“…Satellite data, once validated, will provide a highly accurate and grounding knowledge for effective and efficient global understanding of microplastics associated risks and consequences, as already happening in various disciplines with other satellite-based data. In this context, any synergy among scientists and the most influential space agencies resulting into more suitable monitoring tool application and practice have been, and must be, encouraged and strengthened 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Satellite data, once validated, will provide a highly accurate and grounding knowledge for effective and efficient global understanding of microplastics associated risks and consequences, as already happening in various disciplines with other satellite-based data. In this context, any synergy among scientists and the most influential space agencies resulting into more suitable monitoring tool application and practice have been, and must be, encouraged and strengthened 34 .…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, precise information is still required on the spatial and temporal extent of the storage of macroplastic debris in river deposits (both surface and subsurface) and riparian vegetation, and the estimation of the potential for macroplastic remobilization caused by water inundation and erosion processes. Recent works showed that macroplastic debris can be detected through visual analysis of present and past sediments [1,21,34], and monitored and mapped with remote sensing methods (e.g., aerial photographs, UAV surveys) [35][36][37][38][39][40][41], thus creating a promising methodological perspective for future research. However, a conceptual framework and a theoretical background for research on macroplastic storage and remobilization in fluvial systems are not available.…”
Section: Introductionmentioning
confidence: 99%
“…The newly introduced remote sensing method can detect floating MPs of the coastal water surface using a satellite subpixel scale image. In this analysis, the Naive Bayes (Bayesian) algorithm is used to synchronize MPs sensing data and ensures 86% accuracy of detection (Biermann et al 2020). The combination of Raman spectroscopy, auto particle detection, and image analysis is also used for the identification of MPs in different samples.…”
Section: Methods Of Detectionmentioning
confidence: 99%